Temperature feedback control of coated shape memory alloy for micro air vehicle flapping wing - Awang Jumat, Nurkhairunisa (2020)
Micro air vehicle (MAV) flapping wing is a small portable flying vehicle that can be beneficial for different flight missions. Currently, the designers tend to emulate flapping flight of animals in various design using different types of actuation. Due to the size and weight of MAVs, there is a critical need to design a novel actuation mechanism that is able to overcome those constraints. Nowadays, there are few types of actuator that frequently used such as conventional actuator (servo and piezoelectric) and smart actuator (shape memory alloy). For this research work, Shape Memory Alloy (SMA) has been proposed as the actuator due to its low weight and high strain to weight ratio. The objective of this study is to develop actuation mechanism using SMA to achieve desired frequency that is less than 2.5 Hz instead of using conventional actuator which consumes more space for a small size flapping wing. The idea behind this research work is to use proportional, integral and derivative (PID) control via temperature feedback that imitates pulse width modulation (PWM) signal (on-off signal) to actuate flapping wing model at maximum amplitude that will contribute in the high angle of deflection and increase the frequency of the flapping. However since SMA is non-linear in behavior, PWM signal may not be suitable to apply in the control system and thus a control feedback need to be implemented in the actuation system. After reviewing several types of feedback control, temperature feedback has the most potential since the response produce oscillation of amplitude at steady state compared to the other types of feedback control. However, temperature feedback gives few drawbacks such as slow response and difficult to tune the controller in order to reduce steady state error. Since SMA’s behaviour was nonlinear with slow cooling rate and uneven spread of temperature, Encapso K. was used as substitute to polydimethylsiloxane (PDMS) in order to improve the cooling, spread of temperature and response for the SMA actuator which ideally can be used for SMA with temperature up to 90oC during heating. Fabrication of Encapso K. on SMA was done using dip-coating technique. The flapping actuation system was integrated with LabVIEW software and Data Acquisition System (DAQ). Thermocouple was used to monitor the temperature and in order to read the position deflection of composite plate during flapping, strain gauge was used as the sensor. Last but not least, as a proof of concept, the model was tested in wind tunnel in order to test robustness of the actuation control system in the presence of wind flow. This test was conducted for five types of speed for both type of SMA wire which were uncoated and coated. Finally, the obtained results shows that by developing flapping actuation mechanism using PID control temperature feedback system was able to produce the desired oscillatory motion, even in the presence of wind flow at low Reynolds number.